(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article addresses the issue of the relationship between language and culture in world educational dictionaries. Language is the cultural and spiritual wealth of the people in the form of oral and written speech collects, preserves and transmits to the next generation samples of lexicon, phraseology, grammar, fiction. A learner in the process of learning a language, especially a mother tongue the rich cultural heritage passed down from generation to generation also absorbs spiritual values. In the process, along with textbooks, various school dictionaries, information banks, the role of lexical minimums is important. It was scientifically substantiated that the educational dictionary was based on an educational purpose, that the first dictionaries were ancient school textbooks, that they were created for educational purposes, and that later dictionaries became a separate genre away from textbooks and textbooks